Introduction to Latin American Studies and the Humanities: One Year Later - Allison Margaret Bigelow; Thomas Miller Klubock (Latin American Research Review, 2019)
This essay introduces the three essays in this collection, “Latin American Studies and the Humanities: One Year Later.” This collection follows our first dossier, “Latin American Studies and the Humanities: Past, Present, Future,” which was published in September 2018 (https://doi.org/10.25222/larr.521). The essays here—all written by historians—address current questions in humanistic research in Latin American and ethnic/area studies, including object-centered analysis, comparative methodologies, and archival formation and practices. Our introduction situates the essays in the dossier within three critical contexts, suggesting how new work in Latin American studies can engage with diverse scholarly paradigms, frameworks, and methodological approaches, specifically oceanic worlds and science studies, ethnic and area studies, and Latinx studies.   Resumen El presente ensayo proporciona un panorama de los tres artículos históricos que forman este dossier, “Latin American Studies and the Humanities: One Year Later” (Estudios latinoamericanos y las humanidades: Un año después). Los trabajos de la presente colección contestan en cierta manera el dossier que publicamos en septiembre del año pasado bajo el título “Latin American Studies and the Humanities: Past, Present, Future” (Estudios latinoamericanos y las humanidades: Pasado, presente, futuro, disponible en https://doi.org/10.25222/larr.521). Los ensayos del presente dossier, a igual que los de la colección anterior, contribuyen a varios temas actuales en los estudios latinoamericanos, entre ellos el análisis de los objetos, metodologías comparadas y prácticas de archivo. Nuestro ensayo introductorio pretende situar los ensayos dentro de tres contextos críticos, así mostrando cómo diversos abordajes humanísticos y marcos teóricos nos ayudarán entender los vínculos entre los estudios latinoamericanos y tres campos particulares: los paradigmas océanos y los estudios de la historia de la ciencia y tecnología; los estudios de área y etnicidades; los estudios Latinx.